1999
DOI: 10.1097/00005537-199908000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Increased Stability of Airflow Following Botulinum Toxin Injection

Abstract: This finding suggests there is a change in the type, as well as the level, of activity in the muscles of speech production following botulinum toxin injection. The increase in airflow stability identified could be due to increased stability of the laryngeal system and possibly of the respiratory system as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 20 publications
2
21
0
3
Order By: Relevance
“…57 Subjects asked to repeat the same phrase, "Pop took his socks off," several times, emphasizing different syllables, varied their subglottal air pressure at the required moment by squeezing the lungs, while making very little laryngeal adjustment. Such controlled variation in speech intensity is important for the production of language-typical sound modulation, including altering meaning.…”
Section: Modifications To Quiet Breathing For Human Speech Compared Wmentioning
confidence: 99%
“…57 Subjects asked to repeat the same phrase, "Pop took his socks off," several times, emphasizing different syllables, varied their subglottal air pressure at the required moment by squeezing the lungs, while making very little laryngeal adjustment. Such controlled variation in speech intensity is important for the production of language-typical sound modulation, including altering meaning.…”
Section: Modifications To Quiet Breathing For Human Speech Compared Wmentioning
confidence: 99%
“…For spasmodic dysphonia (SD), there is data from several clinical studies and meta-analyses [Wong et al 1995;Brin et al 1998;Whurr et al 1998;Finnegan et al 1999;Boutsen et al 1998;Watts et al 2006Watts et al , 2008Blitzer, 2010]. One double-blind, placebo-controlled study examined the effects of BoNT-A versus saline in 13 adductor SD patients and revealed significant effects of BoNT-A on voice quality, perceived voice improvement and acoustic measurements [Troung et al 1991].…”
Section: Spasmodic Dysphoniamentioning
confidence: 99%
“…O uso de TB é considerado o tratamento mais utilizado para a DLAD (Ludlow et al, 1988;Aronson et al, 1993;Adams et al, 1995;Woodson, 1995;Wong et al, 1995a;Inagi et al, 1996;Lindestad et al, 1997;Zwirner et al, 1997;Finnegan et al, 1999;Ludlow, 2000;Galardi et al, 2001;Langeveld et al, 2001;Boutsen et al, 2002;Tish et al, 2003;Adler et al, 2004;Cannito et al, 2004;Blitzer, 2005;Wingate et al, 2005;Baylor et al, 2007;Cannito et al, 2008;Ludlow et al, 2008;Paniello et al, 2009;Blitzer, 2010;Elmiyeh et al, 2010;Novakovic et al, 2011;Fulmer et al, 2011;Cannito et al, 2012ab;Dejonckere et al, 2012;Gama et al, 2012;Damrose, 2012;Hu et al, 2013;Rosow et al, 2013), sendo aplicado, principalmente, no músculo TA, apresentando alívio dos síntomas no segundo ou terceiro dia. Após a ação do medicamento, o tratamento atinge a estabilidade após duas semanas, quando se percebe melhora na qualidade da voz (Ludlow et al, 1988;Boutsen et al, 2002;Blitzer, 2010;Cannito et al, 2012a).…”
Section: Discussionunclassified
“…Após mais de duas décadas de estudos, ainda não há consenso quanto A identificação dos sinais e sintomas, bem como a eficiência no tratamento com TB para indivíduos com DLAD, tem sido bastante documentada por meio de estudos que apresentam análise perceptivo-auditiva (Ludlow et al,1988;Truong et al 1991;Adams et al,1995;Boutsen et al, 2002;Tish et al, 2003;Cannito et al, 2004;Blitzer, 2005;Eadie et al, 2007;Cannito et al, 2008;Braden et al, 2010;Cannito et al, 2012ab;Silverman et al, 2012;Hu et al, 2013); análise espectrográfica (Ludlow et al, 1988;Boutsen et al, 2002;Cannito et al, 2004;Rees et al, 2007;Cannito et al, 2008;Gama et al, 2012); análise acústica de parâmetros vocais (Adams et al, 1995;Zwirner et al, 1997;Sapienza et al, 1998;Boutsen et al, 2002;Kendall et al, 2011;Cannito et al, 2012ab); parâmetros aerodinâmicos (Finnegan et al, 1999;Boutsen et al, 2002) e impacto vocal na qualidade de vida e autopercepção (Aronson et al, 1993 ;Adams et al, 1995;Liu et al, 1996;Lindestad et al, 1997;Wingate et al, 2005 ;Paniello et al, 2009;Braden et al, 2010;Elmieyeh et al, 2010;Novakovic et al, 2011;Dejonckere et al, 2012;…”
Section: Discussionunclassified
See 1 more Smart Citation